The changing face of biotechnology research at ILRI - Kemp, Stephen J. (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Steve Kemp, reflects on changes in ILRI's biotechnology research over the past ten years.